RATIONAL THERAPY OF HYPERACID GASTRITIS IN PREGNANT WOMEN - Z.M, Usmonova; Oʻgʻli, Rizayev Eldor Sayfulla (PT. Antis International Publisher, 2025)
Objective: The objective of this study is to investigate the causes, diagnostic methods, and treatment strategies for gastritis with high acidity, focusing on its clinical manifestation, diagnosis, and management. Methods: This study uses clinical and instrumental methods for diagnosing gastritis with high acidity, including FEGDS with a pH meter of gastric juice, biopsy of the mucosa, and Helicobacter pylori infection testing. Various treatment approaches, such as dietary modifications, antacids, proton pump inhibitors, gastroprotectors, and antibacterial therapy, are also explored. Results: The results highlight the effectiveness of combining diet modifications, antacids, proton pump inhibitors, and gastroprotectors in managing symptoms of gastritis with high acidity. Additionally, the study emphasizes the importance of detecting and treating Helicobacter pylori infection to prevent further complications. Novelty: This study presents a comprehensive approach to the diagnosis and treatment of gastritis with high acidity, integrating clinical findings with effective management techniques, including the role of sanatorium-resort treatment and physiotherapy during remission periods.